(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The Independence of the Republic of Uzbekistan is a significant event in the history of Central Asia. This article explores the journey of Uzbekistan towards independence, from its Soviet past to its emergence as a sovereign nation. It delves into the national symbols of Uzbekistan, such as the flag, emblem, and anthem, and their cultural and historical significance. The article also discusses the impact of independence on the country's political, economic, and social landscape.